2019
DOI: 10.1002/iju5.12108
|View full text |Cite
|
Sign up to set email alerts
|

Robot‐assisted laparoscopic partial nephrectomy for horseshoe kidney: A case report

Abstract: Introduction Horseshoe kidney has unique anatomical features, such as a complex blood supply. We report a patient with renal cell carcinoma in a horseshoe kidney, who underwent tumor resection by robot‐assisted laparoscopic partial nephrectomy based on preoperative three‐dimensional computed tomography. Case presentation A 66‐year‐old man was referred to our hospital with a 2‐cm enhancing mid‐pole mass in the left moiety of a horseshoe kidney. The clinical diagnosis was renal cell carcinoma cT1aN0M0 (R.E.N.A.L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…The 3D reconstruction images have been published in 6 of 10 previous case reports of LPN or RAPN for HSK. However, there have been only three recent case reports (including the present case) in which the contour and positional relationships among the renal parenchyma, tumor, and renal arteries were clearly identified …”
mentioning
confidence: 65%
See 1 more Smart Citation
“…The 3D reconstruction images have been published in 6 of 10 previous case reports of LPN or RAPN for HSK. However, there have been only three recent case reports (including the present case) in which the contour and positional relationships among the renal parenchyma, tumor, and renal arteries were clearly identified …”
mentioning
confidence: 65%
“…In the present case report, Fujihara et al . reported the third successful case of RAPN for HSK . The renal mass, which had a diameter of 2 cm in the lateral mid‐pole of the left moiety, was resected using the transperitoneal RAPN procedure.…”
mentioning
confidence: 99%
“…Until now, there are only 4 cases that characterizes robot-assisted partial or heminephrectomy for renal tumors with fusion anomalies of the kidney [2,[14][15][16]. Three of them reported the surgery was performed through a transperitoneal approach [14][15][16]. To our knowledge, this is the rst study reported retroperitoneal robotassisted laparoscopic partial nephrectomy with HSK.…”
Section: Discussionmentioning
confidence: 98%
“…Molina WR et al [13] also documented that retroperitoneal approach may work better for tumors located in posterolateral side. Until now, there are only 4 cases that characterizes robot-assisted partial or heminephrectomy for renal tumors with fusion anomalies of the kidney [2,[14][15][16]. Three of them reported the surgery was performed through a transperitoneal approach [14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, only four cases of RAPN in patients with HSK have been described in the literature (Table 1). 11–14 Due to its good visibility with 3D images and free operability of forceps, RAPN has the advantage of resection of the tumor and sutring of renal parenchyma compared with conventional laparoscopic procedures. However, the HSK requires extensive dissection to handle its poor mobility and identification of various vasculatures.…”
Section: Discussionmentioning
confidence: 99%